A lateral load distribution for the static analysis of base-isolated building frames under the effect of far-fault and near-fault ground motions. (December 2021) - Rostami, Afshin; Poursha, Mehdi
Abstract: This paper attempts to examine the effect of the scaling of ground motion records on the seismic responses of base-isolated buildings by using the three scaling methods including the ASCE 7–10, acceleration spectrum intensity, SIa, and the spectral acceleration corresponding to the effective period of the base-isolated structure at the design displacement, Sa (TD ). The buildings had steel moment-resisting and X-braced systems and were isolated with lead rubber bearings (LRBs) at the base. Near-fault ground motions with Forward Directivity (FD), Fling-Step (FS) and No Pulse (No P.) characteristics as well as far-fault ground motion records were studied in this paper. The discrepancy in the seismic responses as well as the effect of the pulse period in the case of pulse-like ground motions was scrutinized for the three scaling methods. Also, the response spectrum analysis (RSA) and static method with the equivalent lateral force distribution prescribed in ASCE 7–10 were carried out. The results indicate that the RSA as well as the static analysis, prescribed in ASCE 7–10, underestimates the story shears of the base-isolated buildings. The underestimation increases in the case of the FF and No P. ground motions having a large amount of spectral acceleration in the higher modes region. Also, the underestimation increases with the increase in the height of the base-isolated buildings as well as in the case of the moment-resisting frames compared to the X-braced ones. Finally, by means of the results derived from the time history analyses, a formula was proposed to determine the lateral force distribution along the height of the base-isolated buildings with LRBs considering the characteristics of the isolator and the structure for different types of the ground motions.